(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Optimistic investors invest their capital into businesses and projects which result into expansion of businesses, create new job possibility and support to the growth and development of the nation economy. Information disclosed by the financial statements enables stakeholders to better understand the performance or otherwise of the business, as well as the assessment of the financial strength and growth potentials of the firm. For any business organization to grow it needs to publish adequate, reliable, clear and fair financial information. Evidence from research showed that most businesses released window dressing financial statement for public consumption without realizing how it would affect them, which result into lack of trust from the investors. This study therefore examined the effect of corporate financial reporting on investor’s confidence of listed consumer goods companies in Nigeria for the period between 2015 – 2024. The study adopted ex post facto research design and the population consisted of 28 listed consumer goods companies upon which 10 companies were selected using purposive sampling techniques. The results from the GMM estimator showed that accounting conservatism and cash flow value have positive and significant effect with the co-efficient (0.0068 and 0.0025) and p-value (0.009 and 0.001) at 5% level of significant respectively. While equity value has negative coefficient -0.6150 but significant with p-value 0.000 at 5% level of significant. The study concluded that corporate financial reporting enhanced investors’ confidence of listed consumer goods companies in Nigeria. The study recommended that companies should prepare their annual financial reports with transparency, truthfulness and without compromising the standard in such a way that investors can place the reliance on the contents of the reports, which will subsequently propel a positive market response and increase their performance.